2023
DOI: 10.3389/fbioe.2023.1091554
|View full text |Cite
|
Sign up to set email alerts
|

From waste to wealth: Repurposing slaughterhouse waste for xenotransplantation

Abstract: Slaughterhouses produce large quantities of biological waste, and most of these materials are underutilized. In many published reports, the possibility of repurposing this form of waste to create biomaterials, fertilizers, biogas, and feeds has been discussed. However, the employment of particular offal wastes in xenotransplantation has yet to be extensively uncovered. Overall, viable transplantable tissues and organs are scarce, and developing bioartificial components using such discarded materials may help i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 182 publications
0
19
0
Order By: Relevance
“…This characteristic supports its conduciveness xenografting [25]. Moreover, recent studies have also revealed the potential to generate a limitless supply of corneal xenografts using slaughterhouse waste [11,[27][28][29][30]. Based on this potential, we assess current applications and performance in preclinical and clinical practices of various decellularization protocols used to create Kpros and their ability to maintain pertinent structural and physiological capacities.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…This characteristic supports its conduciveness xenografting [25]. Moreover, recent studies have also revealed the potential to generate a limitless supply of corneal xenografts using slaughterhouse waste [11,[27][28][29][30]. Based on this potential, we assess current applications and performance in preclinical and clinical practices of various decellularization protocols used to create Kpros and their ability to maintain pertinent structural and physiological capacities.…”
Section: Introductionmentioning
confidence: 79%
“…It provides a more effective alternative to ease the constraints of autologous grafting than synthetic vascular tissue engineering procedures [10,20]. The elimination of cellular components and related waste should reduce any potential host rejection or immune reaction [27]. The purpose of corneal decellularization is to yield biocompatible ECM components that possess latent biochemical cues to support in vivo tissue remodeling and long-term transplantability [10,20].…”
Section: Methods Of Corneal Decellularizationmentioning
confidence: 99%
“…Furthermore, functional cross-linking techniques may generate interconnected fibrillar scaffolds that can support tunable toughness and strength 80 . Likewise, additional coatings can also be employed to reduce scaffold antigenicity 10 and porosity 81 . Again, such coating molecules can be coupled with fluorescent labels for future IVM investigations to gauge their effectiveness in supporting optimized approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Whole organ decellularization has been described as one of the most promising ways to construct a bioartificial kidney 6 . Decellularization focuses on extracting the extracellular matrix (ECM) from the native tissue and organ with as many structural and functional clues as possible 7 10 . The ECM can then be employed as a natural template for regeneration, as observed traditionally in commercial substitutes 11 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A greater understanding of the roles of key signaling pathways has also allowed investigators to differentiate stem cell niches into various lineages. We believe that shortly, organoids derived from patients’ cells will be able to repopulate decellularized renal scaffolds and printed tissues or even be injected back into the patients to restore their native dysfunction ( 69 71 ). Nevertheless, many technical ( 72 – 78 ) and ethical ( 79 87 ) issues still need to be solved in this field.…”
Section: Efforts To Devise Effective Genetic Alterations In the Kidneymentioning
confidence: 99%